Synthesis and Stability of Metal-organic Frameworks (MOFs) Photocatalysts for the Removal of Persistent Organic Pollutants (POPs) from Wastewater - Mukhtar, Ahmad; Ullah, Sami; Al-Sehemi, Abdullah G.; Assiri, Mohammed A.; Saqib, Sidra; Amen, Rabia; Babar, Muhammad; Bustam, Mohamad A.; Ahmad, Tausif (Current Analytical Chemistry, 2021)
Background: The removal of persistent organic pollutants (POPs) from the contaminated water by employing photocatalytic adsorption is considered as one of the most emerging technologies due to its’ cost- and energy-effectiveness. It has attracted significant attention of global researchers to process the world's wastewater. Methods: Among different adsorbents, the metal-organic frameworks (MOFs) have demonstrated remarkable potential and a bright future perspective in the photocatalytic-based adsorptive removal of POPs from wastewater. This review deals with the introduction of MOFs and contaminations in wastewater, followed by the synthesis method for MOFs and their properties. The review is extended to the review of mechanisms for the photocatalytic adsorption along with the recent progress in removal of persistent toxic substances, pesticides, herbicides, phenols, and antibiotics. Furthermore, the future challenges in this promising area are also discussed. Results: Much research work has been done in the area of photocatalytic adsorptive removal of the POPs using the MOFs due to their significant structural and texture properties. Substantial research efforts have been carried out to functionalize the MOFs in order to improve their adsorption potential. Overall, this review demonstrated that the MOFs could be applied successfully for the photocatalytic adsorptive removal of the POPs from contaminated water. Conclusion: Despite the bright future perspective of the MOFs, there are some issues that need to be accounted for: The development of MOFs with redox-active metals and/or organic functionalized ligands, MOFs application for the photocatalytic adsorptive removal of the gaseous contaminants, indepth understanding of the mechanism of the photocatalytic adsorptive removal of the POPs, and the application of the MOFs for photocatalytic adsorptive removal of the POPs in real environmental conditions. The fast development of the MOFs in the recent era indicates a bright future perspective in spite of the challenges in this area.
Keywords: wastewater